Crossing the Cartography of Exile - Mansilla-Miranda, José (Université d'Ottawa / University of Ottawa, 2015)
Crossing the Cartography of Exile explores ideas of territoriality, hybrid identity and transculturation. The thesis and exhibition is the result of two years of Practice-Led Research, which is the performative research methodology, carried in the La Chapelle Woodshop of the 100 Laurier Avenue East Building of the Department of Visual Arts. The building was the former Juniorat du Sacré-Coeur of the Oblates of Mary Immaculate built in 1893-94. The Woodshop is the former chapel of the seminary therefore has references to a place of prayer and worship and for my praxis became a place to re-enact the ancient trade of Joseph the Carpenter. The La Chapelle Shipyard inside the woodshop as mnemonic site became a performative site-specific platform specialized in creating small-scale sculptures with recycled and repourposed shipping pallets and a place in which to connect memory with the ancient trade of a shipwright or shipbuilder. Small-scale sculpture then became a symbolic marker for the intimacy of a personal and free territory made of repurposed shipping pallets. Therefore, by working with recycled changeable materials I fashioned a poetic visual language to enchant the wound of exile.
Keywords: Practice-Led Research; Mnemonic Site; Exile; Recycled Materials; Small-Scale Sculpture; Shipping Pallets